INOVASI PELAYANAN SIM BOOKING DI SATLANTAS POLRES KUDUS - Aron Sebastian (Magister Administrasi Publik, FISIP, 2019)
In order to adapt in changing environment, innovation is an important component in public organization. Innovation in public organization runs in two stages, the initiation stage and the implementation stage. The study examines supporting factors and barriers of innovation at the Driving Licence service agency. The paper analyzes the initiation stage and the implementation stage. In the initiation stage, the article shows the agency’s decision to impement